Analyzing the Impact of Store’s Reputation, Product Price, and Service Standards Towards Customer Repurchase Decision at Brastagi Supermarket (Gatot Subroto Street, Medan) - Karisha Christie; Felicia (MultiTech Publisher, 2019)
Study This aim For know influencing factors _ application standard accountancy finance entity without accountability public . Population palace researcher This is whole cooperative active in the city of Bogor. Whereas For sample study are 83 cooperatives use purposive sampling method . Data analysis technique used in study This is analysis multiple linear regression . Research results show that level education part finance cooperative , age effort , socialization of SAK ETAP and understanding accountancy influential positive and significant in a manner simultaneous to application of SAK ETAP.